2020
DOI: 10.1021/jacs.0c05610
|View full text |Cite
|
Sign up to set email alerts
|

Invoking Side-Chain Functionality for the Mediation of Regioselectivity during Ring-Opening Polymerization of Glucose Carbonates

Abstract: The extent of participation of side-chain functionalities during the 1,5,7-triazabicyclo[5.4.0]­dec-5-ene (TBD) organobase-catalyzed ring-opening polymerizations (ROP) of six-membered cyclic d-glucose-based carbonates was found to result in significantly different regiochemical outcomes. High regioselectivity was observed for naturally derived poly­(4,6-d-glucose carbonate)­s (PGCs) containing carbonate side chain substituents in the 2- and 3-positions, whereas regioirregularity was found for analogous PGCs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 35 publications
2
40
2
Order By: Relevance
“…Recently, we showed that the regiochemistry of TBD-catalyzed ROPs of d -glucose-based 4,6-cyclic carbonates could be tuned by varying the side-chain substituents on the 2- and 3-positions of the sugar ring. 18 Density functional theory (DFT) calculations revealed that the regioselectivity differences may have resulted from intermolecular hydrogen bonding between the carbonate side-chain functionalities and TBD in the transition states. Further investigations are needed to fully understand the mechanistic origins of regiochemical outcomes, and then to translate that information into meaningful adjustments to polymer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that the regiochemistry of TBD-catalyzed ROPs of d -glucose-based 4,6-cyclic carbonates could be tuned by varying the side-chain substituents on the 2- and 3-positions of the sugar ring. 18 Density functional theory (DFT) calculations revealed that the regioselectivity differences may have resulted from intermolecular hydrogen bonding between the carbonate side-chain functionalities and TBD in the transition states. Further investigations are needed to fully understand the mechanistic origins of regiochemical outcomes, and then to translate that information into meaningful adjustments to polymer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ring‐opening polymerization (ROP) of cyclic monomers has been demonstrated as a valid way to synthesize valuable polymer materials [1–21] . The five‐membered propylene carbonate (PC) would be a desirable candidate, benefited from its wide sources (renewable CO 2 ), easy accessibility, low toxicity and broad application [22, 23] .…”
Section: Introductionmentioning
confidence: 99%
“…[5] Unlike their five-membered analogues, the ROP of larger-ring carbonates has been reported as a viable strategy towards the preparation of polycarbonates. [6] In particular, the ROP of six-membered carbonates has been most frequently studied building on a more diverse set of available monomers, thereby creating polycarbonate variability (Scheme 1a). [7] However, the synthesis of six-membered cyclic carbonates (6MCCs) can be tedious and only a handful of effective methods have been reported so far.…”
Section: Introductionmentioning
confidence: 99%